Nurses' Awareness and Participation in Mandatory Continuing Professional Development in the Philippines: A Pilot Survey - Ryan Michael Flores Oducado; Julie Anne Faye Sobrepeña Palma (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2020)
Introduction: Mandatory Continuing Professional Development (CPD) in the Philippines is relatively new. The purpose of the study was to determine nurses' awareness and participation in CPD in the Philippines. Methods: This descriptive survey was conducted among nurses (n=30) in a private hospital in Iloilo City. A researcher-made survey tool was used to gather data. Data were analyzed using descriptive statistics and Mann-Whitney U to test for differences between variables. Results: Results indicated that were nurses were generally aware of the CPD law and its implementing rules and regulations (IRR). However, while nurses understood the concept of CPD and the renewal requirements of the CPD Act, more than half were not aware of learning activities under Self-Directed Learning and that nurses can earn CPD credit units through online CPD programs. Almost half were unaware that excess CPD cannot be carried over to the next three-year period, and more than one-third were unaware that only completed post baccalaureate degree programs can be used to earn CPD credit units. There were no significant differences in the awareness of nurses when grouped according to sex, age, civil status, position, salary, and length of work experience. Seminars and workshops were the most common CPD activities participated by nurses in the last 12 months. Conclusion: Addressing the common information gaps regarding the CPD law identified in this study may assist in increasing nurses' support in the implementation of the mandatory CPD among nurses.